2009
DOI: 10.1093/czoolo/55.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Population response of rodents to control with rodenticides

Abstract: We summarize theoretical approaches and practice of rodent pest control in Russia and former USSR during last 50 years. We review literature as well as original data to understand mechanisms of rodent populations recovery after chemical control campaigns in urban areas, agricultural lands and natural foci of plague. Laboratory and field experiments indicate that inherent individual variation in behavioural, physiological and life-history traits provides survival of heterogeneous mix of individuals in residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…In addition, several studies have investigated the regeneration of fish species after overfishing (Myers et al 1997;Fabrizio et al 2001;Fu et al 2001). In contrast, studies on the population recovery of small rodents after the application of rodenticide are rare and have not been reviewed, apart from that of Shilova and Tchabovsky (2009) for Russia and the former USSR.…”
Section: Population Decline For Conservationmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, several studies have investigated the regeneration of fish species after overfishing (Myers et al 1997;Fabrizio et al 2001;Fu et al 2001). In contrast, studies on the population recovery of small rodents after the application of rodenticide are rare and have not been reviewed, apart from that of Shilova and Tchabovsky (2009) for Russia and the former USSR.…”
Section: Population Decline For Conservationmentioning
confidence: 99%
“…A few studies have suggested that recovery also strongly depends on the species and particular life history strategy, as well as social behaviour (Gardmark et al 2003;Shilova and Tchabovsky 2009).…”
Section: Recovery Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations